2008
DOI: 10.1002/jez.475
|View full text |Cite
|
Sign up to set email alerts
|

Care and parentage in a skin‐feeding caecilian amphibian

Abstract: An exceptional form of parental care has recently been discovered in a poorly known caecilian amphibian. Mothers of the Taita Hills (Kenya) endemic Boulengerula taitanus provide their own skin as a food source for their offspring. Field data suggest that nursing is costly. Females found attending young had a lower body condition and fat body volume than nonbrooding and egg-incubating females, and the female condition decreased substantially during parental care. Most mothers and their eggs or offspring were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…The presence of a deciduous, multicusped, and polystichous juvenile dentition in young Boulengerula taitanus and Siphonops annulatus was one of the key observations leading to the discovery of maternal dermatophagy in these species [3,7,14]. The presence of a similar dentition in young H. squalostoma that were found in association with an attending adult is thus good evidence that this species is similarly dermatophagous.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The presence of a deciduous, multicusped, and polystichous juvenile dentition in young Boulengerula taitanus and Siphonops annulatus was one of the key observations leading to the discovery of maternal dermatophagy in these species [3,7,14]. The presence of a similar dentition in young H. squalostoma that were found in association with an attending adult is thus good evidence that this species is similarly dermatophagous.…”
Section: Discussionmentioning
confidence: 92%
“…The young H. squalostoma were already well developed when the clutch was discovered and lost their deciduous multicusped dentition within one month in captivity at a length of approximately 120 mm and mass of a little over 1 g. We suspect that when they were captured they had been hatched for a considerable time and suggest that weight gain (and maternal weight loss) would have been more noticeable earlier in development. Weight loss has been documented in nursing mothers of B. taitanus [3,14]. Caecilian mothers providing hypertrophied skin to young have been observed to change colour, becoming paler and somewhat "milky" in appearance in both B. taitanus and S. annulatus [3,7].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, little is known on fecundity relations of other oviparous caecilians. Only recently, Kupfer et al (2008) found no size-related fecundity in the oviparous direct-developing caeciliid Boulengerula taitanus. Wake (1980) found an absence of correlation in ovarian clutch size and maternal body size in the derived, viviparous caeciliid Dermophis mexicanus.…”
Section: Discussionmentioning
confidence: 97%
“…An increasing number of studies have shown that polyandry and sperm competition are much more prevalent among amphibians than previously thought [14], [15], [16], [17], [18], [19], [20]. Females are thought to gain indirect genetic benefits from polyandry and a number of studies have shown both good genes and genetic compatibility effects on fertilization success and offspring fitness [14], [18], [21], [22].…”
Section: Introductionmentioning
confidence: 99%